Clinical and Genetic Factors Associated With Thiazide-Induced Hyponatremia. Issue 34 (August 2015) - Huang, Chin-Chou; Chung, Chia-Min; Hung, Shuen-Iu; Pan, Wen-Harn; Leu, Hsin-Bang; Huang, Po-Hsun; Chiu, Chun-Chih; Lin, Liang-Yu; Lin, Chih-Ching; Yang, Chih-Yu; Li, Szu-yuan; Chen, Yen-Chia; et al.
<x xml:space="preserve">Abstract</x> Abstract Thiazide diuretics are associated with an increased risk of hyponatremia. The aim of this study was to investigate possible predictors of thiazide-induced hyponatremia. A total of 48 patients admitted to the ward or to the emergency department due to severe thiazide-induced hyponatremia (Na < 125 mmol/L) were enrolled in our study as the case group. Another 211 hypertensive patients with normal sodium levels after treatment with thiazide diuretics were selected as the control group. Twelve tag single nucleotide polymorphism markers were selected from the Potassium Channel, Inwardly Rectifying Subfamily J, Member 1 (KCNJ1) gene: rs1231254, rs2238009, rs1148058, rs675482, rs673614, rs12795437, rs2855800, rs2509585, rs3016774, rs881333, rs4529890, and rs7116606. Clinical and genetic parameters between patients with thiazide-induced hyponatremia and the control group were compared. Logistic regression was used to analyze data. The patients with thiazide-induced hyponatremia were older (P < 0.001), predominantly female (P = 0.008), had a lower mean body mass index (BMI) (P < 0.001), and more commonly used angiotensin II receptor antagonist (P < 0.001) and spironolactone (P = 0.007) compared with the control groups. Analysis with multivariate logistic regression revealed that age (odds ratio [OR], 1.13; 95% confidence interval [CI], 1.08–1.19, P < 0.001), female gender (OR, 4.49; 95% CI, 1.54–13.11, P = 0.006), BMI (OR, 0.80; 95% CI, 0.69–0.93, P = 0.003), and KCNJ1 rs2509585 C/T or T/T polymorphisms (OR, 5.75; 95% CI, 1.25–26.45, P = 0.03) were independent predictors for thiazide-induced hyponatremia. Older female patients with lower BMIs and KCNJ1 rs2509585 C/T or T/T polymorphisms were more likely to develop thiazide-induced hyponatremia.